The Impact of Profitability and Solvency on the Assets Growth of Sharia Commercial Banks in Indonesia for the 2010–2024 Period - Muharam, Gema Takbir; Juniwati, Endang Hatma (Journal of Applied Islamic Economics and Finance, 2025)
This study examines the phenomena of fluctuations in Return on Assets (ROA) which are not always in line with asset growth in Islamic Commercial Banks (BUS) in Indonesia, as well as the limitations of previous studies that have not analyzed the effect of Debt to Asset Ratio (DAR) on asset growth. The focus of the research is to analyze the effect of profitability and solvency on BUS asset growth for the period 2010-2024. The research objective is to determine the effect of ROA and DAR both partially and simultaneously on BUS asset growth in Indonesia. The research method uses a quantitative approach with panel data regression analysis on 5 Islamic Commercial Banks during the 2010-2024 period using STATA 17, with a total of 75 observations using the Common Effect Model (CEM). The results showed that ROA had a significant positive effect on asset growth, DAR had no effect on asset growth, but simultaneously the two variables had a significant effect on asset growth with a contribution of 14.34%.